ANALISIS KEMAMPUAN BERPIKIR INTUITIF SISWA YANG MEMILIKI GAYA BELAJAR TIPE JUDGING DALAM MENYELESAIKAN SOAL MATEMATIKA DI KELAS X SMA NEGERI 5 BATANGHARI - Khodriyah Khodriyah; Sri Dewi; Hasan Basri Said (PHI: Jurnal Pendidikan Matematika, 2019)
The purpose of this study was to analyze and describe the characters of intuitive thinking students of the type of learning style of judging in solving math problems. The type of research used is descriptive qualitative research. The subject of the study was the tenth grade students of Batanghari 5 State Senior High School with a total of 161 students. Data collection methods used in this study are test methods and interview methods. The research instrument in this study was the researcher himself while the other iinstrument were the MBTI (Myers Briggs Type Indicator) questionnaire which was adopted directly from the Tim Psikologi (Babon Psikotes Paling Update) book, the value of student learning outcomes, mathematics test sheets, and interview guidelines. Intuitive thinking process in solving mathematical problems from the research subject was revealed through observation and interviews based on the task sheet of intuitive thinking ability in solving math problems where the task sheets of students’ intuitive thinking ability in completing math problems and interview guidelines were validated by validator. The data were analyzed based on indicators to solve mathematical problems according to the Polya which included (1) understanding the problem (2) planning the completoin of the problem (3) implementing the problem solving plan (4) reviewing the correctness of the problem that had been made and the intuitive thinking indicator observed  according to Westcott namely (1) catalic inference (2) power of synthesis (3) cammon sense. The results showed that (1) the intuitive thinking characters used by STJ in solving SPLTV questions included: cammon sense, globality, intrinsic certainty and perseverance. (2) the intuitive thinking characters used by SSJ in solving SPLTV problems include: cammon sence, globality.  Keywords:  Intuitive Thinking Ability, Judging Learning Style, Math Problem, Material Three-Variable Linear Equation System.